Insights Into the Role of CSF1R in the Central Nervous System and Neurological Disorders - Hu, Banglian; Duan, Shengshun; Wang, Ziwei; Li, Xin; Zhou, Yuhang; Zhang, Xian; Zhang, Yun-Wu; Xu, Huaxi; Zheng, Honghua (Frontiers in Aging Neuroscience, 2021)
The colony-stimulating factor 1 receptor (CSF1R) is a key tyrosine kinase transmembrane receptor modulating microglial homeostasis, neurogenesis, and neuronal survival in the central nervous system (CNS). CSF1R, which can be proteolytically cleaved into a soluble ectodomain and an intracellular protein fragment, supports the survival of myeloid cells upon activation by two ligands, colony stimulating factor 1 and interleukin 34. CSF1R loss-of-function mutations are the major cause of adult-onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP) and its dysfunction has also been implicated in other neurodegenerative disorders including Alzheimer’s disease (AD). Here, we review the physiological functions of CSF1R in the CNS and its pathological effects in neurological disorders including ALSP, AD, frontotemporal dementia and multiple sclerosis. Understanding the pathophysiology of CSF1R is critical for developing targeted therapies for related neurological diseases.